PENGEMBANGAN MEDIA PEMBELAJARAN E-COMIC PADA MATERI KOSAKATA KONOTATIF DI KELAS V SD - Febi, Febi; Elfia Sukma; Adrias, Adrias; Chandra; M. Habibi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
At the primary school stage, having a strong vocabulary is essential for enhancing kids' language skills. However, in practice, vocabulary learning, especially connotative meaning in Grade V, is still mostly carried out using conventional methods such as textbooks and lectures. This condition tends to reduce students’ participation, interest, and motivation, which affects their understanding of connotative vocabulary. To address this issue, there is a need for creative and interactive online learning materials to establish a more captivating educational setting. The goal of this project is to develop an e-comic as an educational resource to improve students' understanding of connotative language and to evaluate its effectiveness, practicality, and credibility. The study employs the ADDIE framework along with the Research and Development approach. Expert assessment forms were utilized to collect information, surveys for teachers and students were employed to measure feasibility, and the N-Gain formula was applied to assess the effectiveness of the pretest and posttest outcomes. The findings indicate that the e-comic is very effective, earning ratings of 96% for content, 96% for media, and 88% for language features. It is also highly practical, with 100% from teachers and 98% from students. The score from the effectiveness test, known as the N-Gain score, is 0.7542, which puts it among the highest levels. So, the e-comic works well as a learning tool for fifth-grade elementary students.